The Normalities and Abnormalities Associated with Speech in Psychometrically-Defined Schizotypy - Cohen, Alex S. (Schizophr Res, 2014)
Speech deficits are thought to be an important feature of schizotypy – defined as the personality organization reflecting a putative liability for schizophrenia. There is reason to suspect that these deficits manifest as a function of limited cognitive resources. To evaluate this idea, we examined speech from individuals with psychometrically-defined schizotypy during a low cognitively-demanding task versus a relatively high cognitively-demanding task. A range of objective, computer-based measures of speech tapping speech production (silence, number and length of pauses, number and length of utterances), speech variability (global and local intonation and emphasis) and speech content (word fillers, idea density) were employed. Data for control (n=37) and schizotypy (n=39) groups were examined. Results did not confirm our hypotheses. While the cognitive-load task reduced speech expressivity for subjects as a group for most variables, the schizotypy group was not more pathological in speech characteristics compared to the control group. Interestingly, some aspects of speech in schizotypal versus control subjects were healthier under high cognitive load. Moreover, schizotypal subjects performed better, at a trend level, than controls on the cognitively demanding task. These findings hold important implications for our understanding of the neurocognitive architecture associated with the schizophrenia-spectrum. Of particular note concerns the apparent mismatch between self-reported schizotypal traits and objective performance, and the resiliency of speech under cognitive stress in persons with high levels of schizotypy.